Absorptive capacities and the impact of FDI on economic growth - Beatrice Farkas (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This paper analyzes the necessary local conditions required for the existence of positive spillovers from multinationals' entry and it consists of a unified study of absorptive capacities. We start from the idea that FDI speeds up the diffusion of technologies across countries. Yet, the question that arises is: to what extent are these advanced technologies absorbed and successfully internalized by the receiving countries such that they materialize in welfare gains? The impact of FDI depends on the country specific absorptive capacity. We first interact FDI individually with different growth determinants and we find that the contribution of FDI to economic growth is positive and significant depending on the level of human capital and the development of financial markets, but its presence in developing countries must complement rather than substitute a set of other growth determinants. Then we test the robustness of the linear interaction terms relative to each other and we analyze the set of conditions that are most beneficial for FDI.
Keywords: F23; F26; F43; 330; FDI; economic growth; absorptive capacity